Electronic Sourcing as an E-Procurement Practice and Its Role on Organizational Performance - Murithi, Linus Ndege; Ngugi, Patrick Karanja; Kiarie, David (Journal Integration of Social Studies and Business Development, 2024)
State-owned corporations in Kenya are tasked with executing public functions on behalf of the government and supporting the private sector in delivering core commercial services. Procurement processes within these corporations are critical, given that they manage a significant portion of government spending. However, these corporations have been plagued by increased misappropriations, largely due to inefficient procurement practices. One notable weakness is the ineffective sourcing of key suppliers, which has exacerbated these procurement issues. The empirical literature suggests that electronic sourcing can help mitigate inappropriate procurement processes. Nonetheless, this issue has not been thoroughly explored within the Kenyan context, particularly among state corporations. This paper aims to address this gap by assessing the impact of electronic sourcing on the performance of state corporations in Kenya. The study is grounded in dynamic capabilities theory and employs a descriptive correlational research design. Data were collected from a sample of 153 respondents out of a population of 248, using a questionnaire administered physically through a drop-and-pick method. Analysis was conducted using SPSS, with quantitative data evaluated through descriptive statistics (mean and standard deviation) and inferential statistics (regression model). The findings indicate that electronic sourcing significantly affects the performance of state-owned corporations in Kenya. The study concludes that electronic sourcing is crucial for ensuring audit trails, enhancing service delivery, and managing operational costs effectively. Embracing electronic sourcing could, therefore, enable state corporations to improve their performance by becoming more effective in their roles and functions.